UJARAN DAN GERAKAN TUBUH DALAM MENGEKSPRESIKAN KEMARAHAN DALAM FILM THE HUNGER GAMES TRILOGI OLEH SUZANNE COLLINS SUATU ANALISIS PSIKOLINGUISTIK - Marada, Sitti Khomaria (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled â€œUjaran dan Gerakan Tubuh dalam Mengekspresikan Kemarahan dalam Film The Hunger Games Trilogi oleh Suzanne Collinsâ€. Facial emotion and tone of the speech play a major role in expressing these emotions, like sadness, angry, happiness, and disgust, while body movement is the act of generating the information such as facial expression, posture, and gesture. Based on this background, the writer is able to formulate this problem is what kinds of body movements that are used to accompany the speech production of anger in the movie The Hunger Games Trilogy. This objective of research is to analyze the speech and body movements in expressing anger in the movie The Hunger Games Trilogy. This research focuses on the film The Hunger Games Trilogy which consists in three parts. They are The Hunger Games, Catching Fire, and Mockingjay. The research uses descriptive approach in order to find out the speech production and body movements in expressing anger support by Thompson and Yuleâ€™s Theory. The result of this research shows that there are some speeches and body movements which found in expressing anger such as abuse while throwing something by body movement of hands, shout while body movement of pointing the finger, say in harsh manner while body movement of push by hands or foots, and shout while body movement show knife or something by body movement of hands. Â Keywords: Speech, Body Movements, Expression, Anger, The Hunger Games Trilogy, Psycholinguistic Analysis